2018
DOI: 10.1002/oby.22303
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Total Meal Replacement Program (OPTIFAST Program) on Weight Loss: Results from the OPTIWIN Study

Abstract: Objective The aim of this study was to test the effectiveness of the OPTIFAST program (OP), a total meal replacement dietary intervention, compared with a food‐based (FB) dietary plan for weight loss. Methods Participants with BMI 30 to 55 kg/m2, age 18 to 70 years old, were randomized to OP or FB dietary and lifestyle interventions for 26 weeks, followed by a weight‐maintenance phase. Outcomes were percent change in body weight (%WL) from baseline to weeks 26 and 52, associated changes in body composition (us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 21 publications
4
70
0
11
Order By: Relevance
“…Um nachhaltig von Maßnahmen zur Gewichtsreduktion profitieren zu können, sollte nach der S3-Leitlinie zur "Prävention und Therapie der Adipositas" eine langfristige Stabilisierung des reduzierten Körpergewichts angestrebt werden [4]. Die Literatur weist eine Vielzahl von Veröffentlichungen verschiedener Gewichtsreduktionsmaßnahmen auf, die jedoch meist nur einen kurzen Untersuchungszeitraum von bis zu 1 Jahr umfassen [5,[15][16][17][18][19][20][21][22][23][24][25][26]. Eine Ursache kann darin gesehen werden, dass Adipositastherapieprogramme oftmals nur auf maximal 1 Jahr ausgelegt sind [4,16,18,27], was langfristige Erfolge erschwert.…”
Section: Diskussionunclassified
See 2 more Smart Citations
“…Um nachhaltig von Maßnahmen zur Gewichtsreduktion profitieren zu können, sollte nach der S3-Leitlinie zur "Prävention und Therapie der Adipositas" eine langfristige Stabilisierung des reduzierten Körpergewichts angestrebt werden [4]. Die Literatur weist eine Vielzahl von Veröffentlichungen verschiedener Gewichtsreduktionsmaßnahmen auf, die jedoch meist nur einen kurzen Untersuchungszeitraum von bis zu 1 Jahr umfassen [5,[15][16][17][18][19][20][21][22][23][24][25][26]. Eine Ursache kann darin gesehen werden, dass Adipositastherapieprogramme oftmals nur auf maximal 1 Jahr ausgelegt sind [4,16,18,27], was langfristige Erfolge erschwert.…”
Section: Diskussionunclassified
“…Auch die Darstellung der Therapieziele sowie der Erfolgskriterien bestätigen den Erfolg des Programms. Im Gegensatz zu dem vorgestellten Programm, erfüllten Programme, die alleinig auf Ernährungsumstellung und/oder Steigerung der Bewegungsaktivität basieren, die Erfolgskriterien bereits nach 1 Jahr zumeist nicht [15,19,22,25,31,34]. Das Studiendesign dieser Arbeit weist einige Schwächen auf.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…The weight regain, especially between 12-and 24 months in the PsA patients, is a marker of a lowering of adherence to the energy intake restriction given during the rst year. It is a well-documented challenge to keep weight off, even in structured weight loss programs [32,33] Dansinger et al found that self-reported dietary adherence was associated with 12-month weight change independent of macronutrient composition of the diet. [34] At the 24-month visit 40% of the PsA patients still had a weight reduction of 10% or more compared to baseline in the present study.…”
Section: Change In Variables Associated With the Metabolic Syndromementioning
confidence: 99%
“…Several studies in both specialist and primary care have included VLED as part of a structured weight loss program for subjects with severe obesity and have shown clinically meaningful weight loss, and the results of the present study are comparable with those. [32,33,[35][36][37] Given the di culties to treat obesity in a longer perspective once it is established, more attention should be given to prevent weight gain and the development of obesity in patients with psoriasis and PsA. We propose that the patients should be informed about the unfavourable effects of obesity on disease course and cardiovascular risk during patient educational programs and that body weight should be routinely measured and discussed during medical follow-ups.…”
Section: Change In Variables Associated With the Metabolic Syndromementioning
confidence: 99%